Hidrogel Sebagai Media Tanam Alternatif Di Perumahan - Diah Harmawati; Dewi Puji Rahayu (Lembaga Pengembangan Kinerja Dosen, 2024)
Hydrogel is a water medium that functions to absorb water and nutrients for plants and release them slowly according to plant needs. Participants were elementary school age children in the Lampu Satu Indah housing complex in Merauke. The method uses lectures and practice. The socialization activities were carried out well, the participants were very enthusiastic. After participating in the socialization activities, participants gained new experiences and new knowledge.